Paisagem da destruição: autobiografia do desastre de Fundão no contexto de Mariana/MG - Celiane Souza Xavier (2020)
We configure ourselves as a suicidal society. This is what the events of the last few years have sought to warn against the overvaluation of the economy in the face of the real demands of global society. The fact is that the growing human ambition has taught us to take a covetous look at nature and its attributes. As a consequence, this account has been impassively charged. Sometimes, due to the action of nature itself when natural disasters occur. In others, as a result of our own actions when we humans manufacture our own ruin. In the midst of the consequences of these machinations, we can mention the current mineral mining collapse, characterized by copious structural ruptures in mining dams that occurred recently in the state, such as the Fundão Dam rupture, in 2015, in the municipality of Mariana. Much has been discussed about it and there is still debate about the causes that caused the structure to collapse. Despite this lack of definition, the accelerated global race towards the accumulation and reproduction of capital has evidently influenced the configuration of the crime disaster. Before him, the increase in extractive-mineral benefits camouflaged, for many centuries, the considerable damaging consequences of the practice for already consolidated territories and for the production of new territorial organizations. For its action, it forced us to experience, on an expanded scale, the costs of operating an economic model that, although a predator, has been privileged throughout history. However, just in time to take on new stances, we are beginning to realize that economic overvaluation can be, as has been the case with Brazilian mining, a time bomb. Today, almost five years after the structural rupture in Fundão, we will see in this study that Mariana and the people affected still feel the consequences of the disaster through violations and situations that, in addition to those immediately perceived, extend over time. In this way, this dissertation proposes to underline the harmful capacity that Brazilian mining has, in the current mold, to interfere in the landscape and in the territory. This with the specific objective of identifying, in the context of the municipality of Mariana, elements of inscription that mark, in the municipal landscape, the resignification of the local reality after the rupture of the dam. To this end, an expanded and multidisciplinary perception of the term landscape and its territorial qualities will be essential - objective conditions for delineating the concept "Landscape of Destruction" as a unit of practical analysis created to achieve the aims of this study. Therefore, a combination of methodological strategies based on the act of moving adrift through the studied territory will also be necessary, aiming at integrating the inseparable theoretical and field works. As a result, we will have the portrait of the Landscape of Destruction in Mariana, which will not only prove the harmful consequences of capitalist impositions on the territories, but will also show, through the identification of the traces of the rupture in Fundão, the creative molds involved in the current massive destruction a that our territories of belonging are subjected.